2011
DOI: 10.1590/s1806-83242011000500007
|View full text |Cite
|
Sign up to set email alerts
|

Response of peripheral blood mononuclear cells to conditioned medium from cultured oral squamous cell carcinomas

Abstract: Response of peripheral blood mononuclear cells to conditioned medium from cultured oral squamous cell carcinomas Abstract: The current study investigated the capacity for tumor factors secreted by head and neck squamous cell carcinoma (HNSCC) cell lines, KB, KB16, and HEP, to induce the secretion of various cytokines from peripheral blood mononuclear cells (PBMCs). PBMCs were isolated from blood samples collected from six healthy volunteers and these cells were incubated for 6, 24, 48, or 72 hours in the prese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 15 publications
1
2
0
Order By: Relevance
“…The higher proliferation of M-406 cells observed when cultured with CMO from both Naïve CBi/L and CBi mice indicates that these media would contain factor/s like IL-2, IL-4, INF-γ, IL-10, TNF-α and many others, yet to be identified, capable to stimulate or inhibit tumor growth. This observation agrees with the results obtained by Franca [24] who found that direct contact between fresh human mononuclear cells and conditioned media from tumor cells induces the secretion of TNF-α and VEGF, factors which are clearly involved in tumor growth.…”
Section: Discussionsupporting
confidence: 93%
“…The higher proliferation of M-406 cells observed when cultured with CMO from both Naïve CBi/L and CBi mice indicates that these media would contain factor/s like IL-2, IL-4, INF-γ, IL-10, TNF-α and many others, yet to be identified, capable to stimulate or inhibit tumor growth. This observation agrees with the results obtained by Franca [24] who found that direct contact between fresh human mononuclear cells and conditioned media from tumor cells induces the secretion of TNF-α and VEGF, factors which are clearly involved in tumor growth.…”
Section: Discussionsupporting
confidence: 93%
“…Upregulation of this gene cluster caused increased recruitment of lymphocytes to the site of injury 29 . In addition, several of the immune‐stimulating cytokines/chemokines identified to be potential IRF5 target genes by RT‐qPCR array (Table 1) have been shown to be expressed in normal head and neck squamous epithelial cells, fallopian tubes, vaginal, corneal, stomach, lung, salivary, colon and pancreatic epithelial cells as well 29 , 31 , 36 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 . These data suggest that IRF5 may have an important and more global role in the regulation of epithelial‐mediated inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…Data obtained from the focused RT‐qPCR array offer significant insight into the complexity of the tumor immune microenvironment; every ligand and receptor listed has the ability to shape an immune response. For instance, the release of IL‐33 from necrotic cells, such as the necrotic and hypoxic cells in the tumor center, along with the chemokine CXCL5, can cause a rapid influx of macrophages and thus a rapid inflammatory response 30 , 31 , 32 , 37 , 38 , 39 , 54 , 55 , 62 , 63 , 64 . Interferon‐γ has been shown to inhibit breast cancer cell growth, 65 whereas CXCR2 () allows for sustained senescence in otherwise neoplastic breast tumors 66 .…”
Section: Discussionmentioning
confidence: 99%